Enhancing Employee Performance at PT. Multicentral Aryaguna: The Role of Skills, Motivation, and the Work Environment - Pawit Winarto; Fransiska Dwi Ayuningtyas; Moh Ali Imron; Sari Maemunah (Human Capital and Organizations, 2026)
This study aims to examine the influence of individual characteristics and the work environment on employee performance at PT. Multicentral Aryaguna. Individual characteristics refer to employees’ abilities, skills, work experience, motivation, and attitudes, while the work environment encompasses both physical aspects, such as lighting, workspace, and facilities, and non-physical aspects, including communication, interpersonal relationships, and organizational climate. This research adopts a quantitative approach using a saturated sampling technique, involving all 35 employees as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings indicate that both individual characteristics and the work environment positively influence employee performance, both partially and simultaneously. These results highlight that employees with strong competencies and positive attitudes, supported by a conducive and well-managed work environment, tend to demonstrate higher levels of productivity and effectiveness in completing their tasks. Furthermore, the study emphasizes the importance of integrating internal and external factors in improving performance outcomes. Therefore, organizations are encouraged to prioritize employee development through continuous training and skill enhancement, while also fostering a supportive and comfortable work environment to optimize performance and achieve organizational goals sustainably